PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN IKLIM ORGANISASI TERHADAP KINERJA DOSEN - Masduki Asbari (Journal Of Communication Education, 2019)
ABSTRACT The qualified performance of lecturers is needed by the university to raise the lecturer itself academic qualification performance, the institution performance and satisfaction of the stakeholders. There are some factors which can accomplish the lecturer's performance, such as transformational leadership and organizational climate. This research tested the effect of transformational leadership and organizational climate on the performance of lecturers by taking Universitas Muhammadiyah Tangerang as a case. Population and sample is 172 lecturers of Universitas Muhammadiyah Tangerang with census method. The statistic approach of the research is simple and multiple linear regression with SPSS 16.0 for Windows program to process the data. The result was transformational leadership gave a positive effect and significant on the organizational climate. The transformational leadership and the organizational climate also gave a positive effect and significant on the performance of lecturers partially and simultaneous. The conclusion is a better lecturer's performance on a higher education especially at Universitas Muhammadiyah Tangerang will be reached if the organization leader can implement a suitable transformational leadership and positive organizational climate, so that the Tri Dharma Perguruan Tinggi which is the goal of each lecturer can be accomplished. Keywords : transformational leadership, organizational climate, lecturer's performance,higher education